Designing a Finished Goods Warehouse Management System to Reduce Paper Waste Using the Framework for the Application of System Thinking: A Case Study at PT XYZ - Wahyuni, Delia Tri Puspa; Handayani, Melia; Ma’ruf, Ma’ruf (Industrial and Domestic Waste Management, 2025)
Digital transformation in Indonesia's manufacturing sector has accelerated the adoption of warehouse management systems, with the automated warehouse market projected to grow from USD 25.6 billion in 2025 to USD 54.3 billion in 2031. Traditional paper-based warehouse operations created inefficiencies, environmental degradation, and operational challenges, including poor traceability, coordination gaps, and significant paper waste. This research aimed to design a comprehensive Finished Goods Warehouse Management System integrated with Outgoing Quality Control (OQC) functionality to address operational challenges at PT. XYZ, including limited human resources, inconsistent inspection duration, inadequate location tracking, and excessive paper consumption of approximately 200 sheets per month. The study employed a qualitative case study approach using the Framework for the Application of System Thinking (FAST) methodology, encompassing Scope Definition, Problem Analysis, Requirements Analysis, and Logical Design phases. The PIECES framework was used to evaluate system feasibility across Performance, Information, Economics, Control, Efficiency, and Service dimensions. Data collection involved observation, semi-structured interviews with warehouse administrators, quality control staff, OQC personnel, and production planning and inventory control (PPIC) staff, along with document review. The research produced comprehensive system models, including use case diagrams, activity diagrams, sequence diagrams, Entity Relationship Diagrams, Data Flow Diagrams, and user interface prototypes. The designed system integrated real-time status updates, automatic blocking mechanisms, barcode scanning technology, digital inspection forms with AQL-based auto-calculation, and complete traceability throughout the supply chain.The integrated WMS design provided practical solutions for improving operational efficiency, eliminating paper waste, ensuring product quality through mandatory quality control integration, and supporting sustainable manufacturing practices in the plastic injection molding industry.